Spine Surgeon Treatment Variability: The Impact on Costs. Issue 5 (August 2018) - Alvin, Matthew D.; Lubelski, Daniel; Alam, Ridwan; Williams, Seth K.; Obuchowski, Nancy A.; Steinmetz, Michael P.; Wang, Jeffrey C.; Melillo, Alfred J.; Pahwa, Amit; Benzel, Edward C.; Modic, Michael T.; Quencer, Robert; et al.
Study Design: Cross-sectional analysis. Objectives: Given the lack of strong evidence/guidelines on appropriate treatment for lumbar spine disease, substantial variability exists among surgical treatments utilized, which is associated with differences in costs to treat a given pathology. Our goal was to investigate the variability in costs among spine surgeons nationally for the same pathology in similar patients. Methods: Four hundred forty-five spine surgeons completed a survey of clinical and radiographic case scenarios on patients with recurrent lumbar disc herniation, low back pain, and spondylolisthesis. Those surveyed were asked to provide various details including their geographical location, specialty, and fellowship training. Treatment options included no surgery, anterior lumbar interbody fusion, posterolateral fusion, and transforaminal/posterior lumbar interbody fusion. Costs were estimated via Medicare national payment amounts. Results: For recurrent lumbar disc herniation, no difference in costs existed for patients undergoing their first revision microdiscectomy. However, for patients undergoing another microdiscectomy, surgeons who operated <100 times/year had significantly lower costs than those who operated >200 times/year ( P < .001) and those with 5-15 years of experience had significantly higher costs than those with >15 years ( P < .001). For the treatment of low back pain, academic surgeons kept costs about 55% lower than private practice surgeons ( P < .001). In the treatment of spondylolisthesis, there was significant treatment variability without significant differences in costs. Conclusions: Significant variability in surgical treatment paradigms exists for different pathologies. Understanding why variability in treatment selection exists in similar clinical contexts across practices is important to ensure the most cost-effective delivery of care among spine surgeons.